2010
DOI: 10.1002/cncy.20046
|View full text |Cite
|
Sign up to set email alerts
|

UbcH10 expression on thyroid fine‐needle aspirates

Abstract: BACKGROUND:Thyroid fine‐needle aspiration (FNA) samples belonging to the follicular neoplasm/suspicious for malignancy classes are controversial. The authors identified UbcH10 as a marker useful in the diagnosis of several neoplasms, including thyroid cancer. Here, analysis of UbcH10 expression by quantitative reverse transcriptase polymerase chain reaction (RT‐PCR) and immunohistochemistry was applied to FNAs.METHODS:A series of 84 follicular neoplasm/suspicious for malignancy FNAs with histological follow‐up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…45,46 However, neither has demonstrated sufficiently high sensitivity or specificity to justify widespread use. Nonetheless, their combined use, along with other markers, continues to be explored.…”
Section: Transcriptional Levelmentioning
confidence: 99%
“…45,46 However, neither has demonstrated sufficiently high sensitivity or specificity to justify widespread use. Nonetheless, their combined use, along with other markers, continues to be explored.…”
Section: Transcriptional Levelmentioning
confidence: 99%
“…Overexpression of UBE2C has been demonstrated in a variety of malignancies such as colorectal, thyroid, lung, breast, ovary and lymphomas corresponding to their normal tissues (Warrenfeltz et al 630 M. V. Bose et al . 2004, Kadara et al 2009, Loussouarn et al 2009, Troncone et al 2009, Chen et al 2010, Guerriero et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…All samples were indeterminate lesions with a cytopathological diagnosis of follicular neoplasm or suspicious for malignancy (Bethesda IV and V). Sensitivity and specificity for classifying indeterminate nodules remained fairly low at 72 and 67%, respectively [55]. The study's authors suggested that UbcH10 could, however, be added as a useful adjunct to other gene panels.…”
Section: Ubch10mentioning
confidence: 96%
“…UBE2C (or UbcH10) is associated with destruction of cell cycle cyclins and facilitation of cell cycle progression [55]. One study by Guerriero et al examined UbcH10 expression using RT-PCR and immunohistochemistry in 84 FNA samples.…”
Section: Ubch10mentioning
confidence: 98%